Notch fatigue of ultrahigh molecular weight polyethylene (UHMWPE) used in total joint replacements. (July 2016) - Ansari, Farzana; Gludovatz, Bernd; Kozak, Adam; Ritchie, Robert O.; Pruitt, Lisa A.
Abstract: Ultrahigh molecular weight polyethylene (UHMWPE) has remained the primary polymer used in hip, knee and shoulder replacements for over 50 years. Recent case studies have demonstrated that catastrophic fatigue fracture of the polymer can severely limit device lifetime and are often associated with stress concentration (notches) integrated into the design. This study evaluates the influence of notch geometry on the fatigue of three formulations of UHMWPE that are in use today. A linear-elastic fracture mechanics approach is adopted to evaluate crack propagation as a function of notch root radius, heat treatment and Vitamin E additions. Specifically, a modified stress-intensity factor that accounts for notch geometry was utilized to model the crack driving force. The degree of notch plasticity for each material/notch combination was further evaluated using finite element methods. Experimental evaluation of crack speed as a function of stress intensity was conducted under cyclic tensile loading, taking crack length and notch plasticity into consideration. Results demonstrated that crack propagation in UHMWPE emanating from a notch was primarily affected by microstructural influences (cross-linking) rather than differences in notch geometry.